Numerical Insights into Tunnelling Effects on Cantilever and Soil-Nailed Retaining Walls in Sand: A Comparative Study Under Varying Tunnel Depths - Soomro, Mukhtiar Ali; Soomro, Rizwan Ali; Darban, Sharafat Ali; Kamchoom, Viroon; Detho, Amir; Cui, Zhen Dong (My University, 2026)
The interaction between tunnelling and retaining walls represents a complex soil–structure interaction problem that can significantly influence wall deformation and stability. This study investigates and compares the behaviour of cantilever and soil-nailed retaining walls subjected to tunnel excavation beneath the wall in dry Toyoura sand. A series of three-dimensional finite element analyses was performed using an advanced hypoplastic constitutive model to simulate nonlinear sand behaviour and stress-path dependency. Tunnel depth was varied using cover-to-diameter (C/D) ratios of 1.83, 3.33, 4.83, and 6.33. The computed results show that both retaining systems exhibit similar settlement patterns due to tunnelling, with maximum settlement reaching approximately 22.8 mm in the case of C/D = 4.83. However, soil nailing has limited influence on reducing tunnelling-induced settlement. In contrast, the soil-nailed wall develops larger rotation and overturning response due to tensile forces mobilized in the soil nails by tunnelling-induced ground movement. For the shallowest tunnel case (C/D = 1.83), maximum tensile forces reach approximately 72 kN and 60 kN in the top and middle nails, respectively. Tunnelling also causes significant redistribution of contact pressure and shear stress beneath the wall base, including partial loss of contact for shallow tunnels. In addition, lateral earth pressure increases substantially, resulting in total lateral forces up to 3.3 times the pre-tunnelling values. The results demonstrate that tunnel depth governs the wall response, while soil nailing primarily affects rotational behaviour and internal force development rather than settlement mitigation.
Keywords: retaining structures; settlement; soil nailing C/D ratio; tunnelling; wall stability